Pengaruh Variasi Fraksi Volume Biokomposit Serat Daun Nanas dan Resin Epoxy-polyester Terhadap Kekuatan Tarik dan Densitas - Siburian, Schubert Ariell P.S.; Kencanawati, Cok Istri Putri Kusuma; Negara, Dewa Ngakan Ketut Putra (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract This study investigates the influence of varying volume fractions in biocomposites consisting of pineapple leaf fibers and epoxypolyester resin on the tensile strength and density of the material. An experimental method was used to produce biocomposites with varying volume fractions of pineapple leaf fibers and epoxypolyester resin. The study utilized a mixed epoxy-polyester resin with a ratio of 9:1 and a hardener at a 2:1 ratio as the matrix. The fiber-to-resin composition utilized volume fractions of 5% fiber to 95% resin, 10% fiber to 90% resin, and 15% fiber to 85% resin. The specimens were molded using an acrylic mold with the hand layup technique. Specimen dimensions were based on ASTM D3039 for tensile testing and ASTM D792-08 for density testing. In the tensile test, values for stress, strain, and elastic modulus were obtained. The average tensile stress showed the highest increase at the 10% pineapple leaf fiber fraction, reaching 9.279 MPa, and the lowest at the 15% fiber fraction, with a value of 7.219 MPa. The average strain increased continuously with the addition of fiber volume fractions, with the lowest value at the 5% fiber fraction at 0.072% and the highest at the 15% fiber fraction at 1.297%. For the elastic modulus, the smallest value was obtained at the 15% fiber fraction at 0.679 GPa, while the largest value was obtained at the 5% fiber fraction at 0.328 GPa. In the density test, the lowest value was found at the 5% fiber fraction at 0.768 g/cm³, and the highest density value was found at the 15% fiber fraction at 1.091 g/cm³, with the 10% fiber fraction yielding a value of 1.090 g/cm³. As the volume fraction increased, the resulting density values decreased. Keywords: Pineapple Leaf Fiber, Epoxy-polyester Resin, Tensile Test, Density Test